Development of solderable layer on power MOSFET for double-side bonding. (February 2022) - Kim, Dajung; Won, Mi So; Jang, Jeongki; Kim, Sooseong; Oh, Chulmin
Abstract: The use of power metal oxide semiconductor field effect transistor (MOSFET) packages is being actively explored to improve heat dissipation by fast switching. The double-side cooling package structure of power MOSFETs is considered efficient for heat dissipation, which requires bonding the MOSFET with Cu lead frames on both the top and bottom sides by soldering. Although soldering can typically be performed for the bottom side, it is challenging to perform on the top side due to Al metallization and has, therefore, been rarely reported. In this study, we developed various layers on the top side of a MOSFET to enable soldering between the MOSFET and Cu lead frame to realize a double-side cooling package. After depositing the thin films on the top side of the MOSFET with Ag and Ni materials, we fabricated the double-side package in the form of a TO-263 package to evaluate the electrical characteristics of the power MOSFET. In addition, we fabricated a typical TO-263 package having only the bottom-side cooling structure and compared its performance with that of the double-side cooling structure. Thermal cycle tests were performed up to 1500 cycles for 25 min at each extreme temperature in the −55 to 125 °C range. Electron backscatter diffraction was conducted on Al metallization beneath the solderable layers to analyze the change in the grain orientation and size of the Al layer. In addition, the stress behavior of the Al layer according to the presence of the Ni layer was compared using FEM simulation. Our findings provide the optimal solderable metallization of 600-nm-thick Ni and Ag layers each for bonding on the top layer of a power MOSFET, realizing a double-side cooling package for power MOSFETs. Highlights: Double-side cooling power MOSFET package using Cu lead frame helps heat dissipation. Metallization on MOSFET source of Al layer enables bonding frame and upper side of MOSFET. Proposed package structure improves electrical characteristics and long-term reliability.